Desempenho da colhedora de milho Penha CLM-350: parte I - sistema espigador - Furlani Jr, J.A. [UNESP]; Guimarães Jr, J.B. [UNESP]; Balastreire, L.A. (Universidade de São Paulo (USP), Escola Superior de Agricultura, 1977)
Com o propósito de avaliar a colhedora Penha CLM-350, visando fornecer subsídios aos projetos e usuários, realizou-se o presente trabalho, onde foi estudada a eficácia do sistema espigador, determinando-se a porcentagem de milho colhido para os diversos tratamentos estudados. Definiu-se um parâmetro adimensional U, que é a relação entre a velocidade periférica dos roletes e a velocidade de deslocamento da colhedora. Procurou-se relacionar as diversos tratamentos U, com os valores percentuais de grãos de milho colhidos e perdidos no solo. Os resultados foram estudados através da análise de variância, empregando-se o teste F, aos níveis de 1% e 5% de probabilidade e o teste Tukey para a comparação estatística entre as médias.

This work was designed with the aim of evaluating the performance of the Penha CLM-350 corn combine, to furnish data to designers and users. The efficiency of the ear picking system was studied, and the percentage of the harvested corn was determined for the various treatments considered. A dimensionless U parameter was defined as the ratio between the peripheral speed of the snapping rolls and the speed of the harvester. The U terms were related to the percentages of corn harvested and corn lost on the ground. The analysis of variance with the F test at 1% and 5% probability levels was utilized to analyse the data, and Tukey's test was utilized for comparison between means. The statistical analysis showed that the treatment were not significant for the percentage of harvested corn, the efficiency maintained above 84,42% for the test conditions. For the conditions tested the values were limited by mechanical characteristics of the combine, particularly the transmission ratio. This suggests the design of a mechanism, which should provide the possibility of changing the transmission ratio from the tractor power take-off to the snapping rolls. This would provide a wider range of variation for U and could provide a mathematical relationship with efficiency.
Performance of the Penha CLM-350 corn combine: part I - ear picking system